2020
DOI: 10.29328/journal.ida.1001018
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic characteristics and other factors associated with depressive illness among medical students at the University of Port Harcourt

Abstract: Background: The burden of depression as a mental disorder has continued to increase and constituting an enormous public health concern among all age groups. A number of socio-demographic, and other factors including a stressful and rigorous academic programme or curriculum such as the one run in most medical schools could contribute to the occurrence of depression among medical students. AIM: To determine the socio-demographic and other factors associated with depression among medical students in the Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(82 reference statements)
1
2
0
Order By: Relevance
“…Regarding the age group of the study sample, our result agreed with those of the study conducted by Okafor et al, [10] who shows that the largest percentage was among the study sample with the age group of 20-24 (47.9%).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the age group of the study sample, our result agreed with those of the study conducted by Okafor et al, [10] who shows that the largest percentage was among the study sample with the age group of 20-24 (47.9%).…”
Section: Discussionsupporting
confidence: 92%
“…Less than half of this study's participants (43%) had good knowledge of depression. This is low compared to a study conducted among medical students at the University of Port Harcourt, Nigeria, where the majority of the respondents were found to have a good knowledge of depression [16]. Similarly, another study conducted in South Korea showed that medical students had good knowledge about the etiology of depression and psychiatric medicine [17].…”
Section: Discussionmentioning
confidence: 64%
“…From a psychological perspective, the role of demographic factors in mental illness has been studied [32,33]. Particularly, several works have analyzed the relationship between patients' profile attributes (e.g., age, gender, and personality traits) and the manifestation of their depression [34]. Most of them have found clear differences among distinct groups of people, particularly between men and women [35][36][37].…”
Section: The Role Of Profiling Traits For Depression Detectionmentioning
confidence: 99%